MgO Scattering Effects on CCT Uniformity and Lumen Strength of The Traditional White LED Packages - De, Pham Van; Thinh, Dang Truong; Ho , Sang Dang (Science and Technology Indonesia, 2025)
Scattering of light within white light-emitting diodes (LEDs) is crucial for minimizing internal reflection and ensuring consistent color distribution. Among the array of scattering-induced nanoparticles, magnesium oxide (MgO) stands out for its distinctive scattering performance, positioning it as a promising material in the field of optic fiber sensing. This study investigates the integration of MgO nanoparticles into yellow phosphor films with the aim of augmenting the color uniformity and luminous efficiency of conventional white LEDs, specifically those excited by blue light. Light scattering is evaluated across varying concentrations of MgO within the phosphor layer. Results reveal that manipulation of MgO nanoparticle concentration enables precise control over correlated color temperature (CCT) regulation in white LEDs. Furthermore, the inclusion of MgO nanoparticles reduces the requisite amount of yellow phosphor for LED fabrication, thereby curbing production costs. Significantly, MgO exhibits potential in harmonizing CCT and luminosity in white LEDs. Additionally, there is a marginal improvement in color quality scale with increasing MgO concentration. The optimal MgO concentration for achieving a balance between CCT uniformity, luminosity, and color reproduction parameters is determined to be 7 wt.%.